Management of the quality of professional activity of the personnel of health care institutions (based on the example of Kharkiv National Medical University) - Shalimova , I.M; Shalimova , A.S. (Problems of Engineer-Pedagogical Education, 2023)
In the course of the theoretical analysis of the scientific literature, it was found that the quality of activities of higher education teachers, as well as the quality of education, are recognized as priority directions of the state educational policy. In particular, the National Doctrine of Education Development highlights that the state's efforts in the field of education are aimed at constantly improving its quality, updating its content, enhancing forms of the organization of the educational process, and creating a market for educational services along with its scientific and methodological support. The article defines that the quality of work of teachers at a higher education institution depends on many factors. The teacher must have an appropriate level of professional knowledge and be able to use the latest pedagogical, technical and information technologies in education and upbringing. The article emphasizes that management of the quality of professional activities of teachers at institutions of higher medical education in modern market conditions is ensured by the application of a set of scientific approaches (systemic, humanistic, personal, democratic, etc.), principles (innovation, stimulation, modeling) and functions (diagnosis, analysis, informing, motivating, forecasting), which contribute to raising the level of their professional pedagogical activity. The article substantiates the conditions for ensuring the quality of higher medical education, namely: the study of the professional needs and interests of pedagogical workers, formation of their work motives, vision of their career prospects, and their active engagement in innovative educational activities.